Case Study: Developing Computational Thinking Skill During Pandemic Situation - Mharta Adji Wardana; Iwan Pranoto (SEAMEO Regional Centre for QITEP in Mathematics, 2020)
Computational thinking, as proposed by Seymour Papert in 1980, is the idea where the interaction between a student and computer can become a mental model, assisting the learning process. This idea becomes well known as constructivism. Thus, Papert believes that the computer presence or even the thinking of computer interaction may help the student think and learn better. It is more general than the present widely accepted perception of computational thinking, where it focuses on the utilization of computers in problem-solving only. This case study aims to describe how students can learn computational thinking through traditional curriculum and unplugged setting in this pandemic situation. Three middle school students participated in a concrete math lesson design in middle school lesson on linear function topic. The result indicates that….